Melatonin prevents neutrophil-mediated oxidative injury in Escherichia coli-induced pyelonephritis in rats - (:unkn) unknown (WILEY, 2006)
Regarding the mechanisms of renal scarring in pyelonephritis, several hypotheses have been put forward, among which oxidative stress is prominent. The present study investigated the possible protective effect of melatonin treatment against Escherichia coli- induced oxidative injury and scarring in renal tissue. For this purpose, 0.1 mL E. coli (ATCC 25922; 10 10 colony-forming units/mL) or saline was injected directly into the renal parenchyma of Wistar rats. Pyelonephritic rats were treated with either saline or melatonin (10 mg/ kg) intraperitoneally. Twenty-four hours or 1 wk after E. Coli injection, rats were decapitated and trunk blood samples were collected for BUN, creatinine, tumor necrosis factor- alpha (TNF-alpha) and lactate dehydrogenase (LDH) determination. In kidney samples, histological analysis was performed, and malondialdehyde (MDA), glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen contents were measured. Formation of reactive oxygen species was monitored using a chemiluminescence (CL) technique. Escherichia Coli inoculation caused a significant reduction in renal GSH levels, which was accompanied by significant increases in MDA levels, MPO activity, CL levels and collagen content of the renal tissues (P < 0.05-0.001). Similarly, serum TNF-a and, LDH, BUN and creatinine levels were elevated in the pyelonephritic rats when compared with control animals. Melatonin treatment reversed all these biochemical indices, as well as histopathological alterations induced by acute pyelonephritis. The protective effects of melatonin can be ascribed to its ability to inhibit neutrophil infilltration, to balance the oxidant-antioxidant status, and to regulate the generation of in. ammatory mediators, suggesting a future role for melatonin in the treatment of acute pyelonephritis.
Keywords: antioxidants; Escherichia coli; glutathione; lipid peroxidation; melatonin; myeloperoxidase; pyelonephritis; tumor necrosis factor-alpha; MICROSOMAL MEMBRANE-FLUIDITY; REACTIVE OXYGEN; MYELOPEROXIDASE; SUPPRESSION; MECHANISMS; VITAMINS; OXIDANT; DAMAGE; MODEL